Congestion-Prone Services Under Quality Competition A Microeconomic Analysis - Moon, Dong-Joo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This study presents new microeconomic analyses of congestion-prone services that comprise most private and public services at the final consumption stage. It accounts for two distinctive features of congestion-prone services: the discrepancy between capacity and throughput, and service quality competition. To accommodate these features, a series of new decision-making theorems for consumers and suppliers is developed. The resulting demand and cost functions incorporate service time as the variable that reflects congestion and service quality. In market equilibrium, interactions between consumers and firms endogenously determine the industrial organization type of each firm and thus allow the coexistence of multiple industrial organization types in the same market. Efficiency of resource allocation is assessed by applying two different criteria: service quality diversity throughout the market and Pareto optimality in each submarket.
Introduction -- Part I: Service Demand of Consumers -- Part II: Cost Analyses for Congestion-Prone Service Systems -- Part III: Decisions of Congestion-Prone Service Firms -- Part IV: Social Welfare Issues for Congestion-Prone Services -- References -- Index.
Keywords: Economics; Industrial organization (Economic theory).; Regional economics; Economics/Management Science; Regional/Spatial Science; Industrial Organization